Influence of temporal parameters of laser irradiation on emission spectra of the evaporated material - Zabello, E.; Syaber, V.; Khizhnyak, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The results of study of the emission spectra of metals excited by laser pulses bursts under atmospheric conditions are presented. It is demonstrated that the area responsible for the atom irradiation of evaporated substance is essentially distant from that of the continual spectrum irradiation. As a result, the sensitivity of the qualitative analysis increases. For quantitative analysis it is necessary to select the analytical lines differing from those used for spark or arc emission analysis.